If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(2x) + -12 = 0 Remove parenthesis around (2x) 3 * 2x + -12 = 0 Multiply 3 * 2 6x + -12 = 0 Reorder the terms: -12 + 6x = 0 Solving -12 + 6x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '12' to each side of the equation. -12 + 12 + 6x = 0 + 12 Combine like terms: -12 + 12 = 0 0 + 6x = 0 + 12 6x = 0 + 12 Combine like terms: 0 + 12 = 12 6x = 12 Divide each side by '6'. x = 2 Simplifying x = 2
| 2x^2+6-71=0 | | f(12)=3x-9 | | 81-(a-3)= | | 2(2x-3)+1=-3x+7(x-2) | | 2x+6x=64 | | X(-4)=-20 | | n/3=14 | | 5z+125+9z+10=135 | | 28=x^2-3x | | x+(8x)=102 | | 8x+16y+z-400=0 | | 219=126-v | | (3x+4)(2x^2-13x+21)=0 | | 0.5(5-7)=8-1(4x+6) | | -14=2v-8 | | 81+(a-3)= | | x+8x=102 | | 2(8b+7)+6b=5(3b+6) | | 6=6t | | 2n/3=16 | | 5u-u=u | | 56/m | | 6x-17=x | | 10x-6=3(5+3x) | | (a+1)*8-7a= | | 4x^3-9x^2+1=0 | | 4x-2x+10=12 | | x^12-64=0 | | 2.5x+3.5x=11.94 | | (a+15)*2+5a= | | 4x+20x=36 | | 2(l+(l-12))=64 |